Competency Requirement for Project Manager in Improving Sustainable Construction Project Success - Norliana Sarpin; Hasan, Ahmad Shawqee; Mohd Iskak, Mohd Afiq (International Journal of Sustainable Construction Engineering and Technology, 2022)
The role of project manager become more complex as the construction industry is focusing on sustainable development. Competencies of a project manager are critical in reducing the encountered challenges in improving sustainable construction project success. However, lack of competency among project managers and mismanagement are among critical problems in the Malaysian construction industry. Therefore, the objectives of this study were to identify the key competencies needed by the project managers in managing the sustainable projects, to examine the key challenges for the project manager and to suggest the strategies for project managers in undertaking a successful sustainable construction project. The scope of this research is among the sustainable construction project practitioners in Kuala Lumpur due to the highest number of sustainable projects registered as recorded in the latest executive summary of the Green Building Index (GBI). The quantitative method was used to collect data from respondents by distributing questionnaires through e-mail and WhatsApp applications. The collected data from 47 responses which representing 31% of the sample size was analyzed using Statistical Package for Social Science (SPSS). The results of the study have shown the key competencies needed by the project managers in successfully managing sustainable construction projects are namely professionalism, emotional resilience and stress tolerance and negotiation skills. The study also identified the key challenges for project managers are including inefficient decision-making and lack of sustainability concept knowledge. In addition, the research also suggested some strategies for project managers to undertake sustainable construction project includes analyzing and mitigating the threat, corrective action plan, and efficient resource allocation. In conclusion, all parties in the construction industry especially project manager needs to play an important role in improving their competency towards the success of sustainable construction project in Malaysia.